2016
DOI: 10.1177/0954411916628559
|View full text |Cite
|
Sign up to set email alerts
|

Measurement outcomes from hip simulators

Abstract: Simulation of wear in total hip replacements has been recognised as an important factor in determining the likelihood of clinical success. However, accurate measurement of wear can be problematic with factors such as number and morphology of wear particles produced as well as ion release proving more important in the biological response to hip replacements than wear volume or wear rate alone. In this study, hard-on-hard (CoCr alloy, AgCrN coating) and hard-on-soft (CoCr alloy and CrN coating on vitamin E blend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…27 Third, the size of the polyethylene wear debris was not measured in this study, and the size of these particulates is an important factor in determining host response and risk of osteolysis. 58 Finally, only one implant size was investigated in this study, so it is currently unknown how different implant sizes would affect wear rates.…”
Section: Discussionmentioning
confidence: 99%
“…27 Third, the size of the polyethylene wear debris was not measured in this study, and the size of these particulates is an important factor in determining host response and risk of osteolysis. 58 Finally, only one implant size was investigated in this study, so it is currently unknown how different implant sizes would affect wear rates.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate total volumetric wear, cobalt and chromium levels in hip simulator lubricant fluid were determined by ICP‐MS and assumed to comprise approximately 92% of total metal in the alloy according to ASTM standards for wrought CoCr alloys used for surgical implants . Previous studies have indicated that the cobalt concentration in hip simulator fluid is highly correlated with wear rates …”
Section: Methodsmentioning
confidence: 99%
“…51,52 Previous studies have indicated that the cobalt concentration in hip simulator fluid is highly correlated with wear rates. 47,52,53…”
Section: Particle Characterization and Elemental Analysismentioning
confidence: 99%
“…Saikko [30] demonstrated that under adverse loading conditions the gravimetric wear rate was not able to show a difference in performance of simulator tested hard-on-hard bearings unless the testing conditions passed a so-V et al [31] have also shown evidence of material degradation in hard-on-hard bearings with AgCrN coatings, despite no visible damage or gravimetric mass loss. Changes of the sliding regime to anything representing less than ideal conditions (i.e.…”
Section: Standard Gait Vs Microseparationmentioning
confidence: 99%
“…As discussed, the industry and research community are becoming increasingly interested in the effects of adverse loading situations and daily living activities on the performance of total hip replacements [23,24,30,31]. A continuous simple twin-peak profile may not be the best method for assessing these devices before they are implanted in patients.…”
Section: Standard Gait Vs Microseparationmentioning
confidence: 99%